Calvin’s instruction on the fifth commandment - Britz, Dolf (Koers, 2014)
In this article Calvin’s explication of the fifth commandment in his works intended to be used in education and catechetical instruction is surveyed. The investigation is restricted to (in this sequence) the 1536 Institutio, the Instruction et Confession de Foy, printed in Geneva in 1537 and 1538, l’Institution puerile de la doctrine Chrestienne and the expanded Institutio (1539) and incorporated Calvin’s exposition of the core biblical texts (Ephesians, Colossians, Exodus and Deuteronomy) used for his explanation of the fifth commandment. The renowned Catechismus (1541/1545) is then scrutinised, followed by a consideration of La maniere d’interroguer les enfans qu’on veut recevoir a la cene Seigneur Iesus Christ (1553). The aim of the research is not limited to a discussion of the content of Calvin’s exposition, but also to establish whether a development can be traced in the theological thinking of Calvin. The conclusion is that Calvin supplemented and clothed the basic trajectories of his interpretation, but that the 1539 Institutio provided the most complete and finalised explication of the fifth commandment. In addition, the conditional obedience of children is omitted in the 1545 Catechismus. It was probably done for pedagogical reasons.